Lunar human landing system architecture tradespace modeling. (April 2021) - Latyshev, Kir; Garzaniti, Nicola; Crawley, Edward; Golkar, Alessandro
Abstract: A renewed interest in lunar exploration with the focus on establishing a constant human presence on the Moon calls for developing new lunar human landing systems (HLS) which would deliver the crew from the prospective Lunar Gateway station to the surface of the Moon and back. Over the years, different human lunar lander architectures were proposed and multiple architecture studies were performed. However, those studies are relevant to the specific assumptions and lunar architectures proposed at the time of conducting the study. Since the current vision for lunar exploration includes new features, such as having the Lunar Gateway and switching to reusable systems, there is a need for a new HLS architecture study. Such studies are being performed by private companies; however, those are rarely publicly available. The goal of this paper is to address this gap and provide a publicly available architectural analysis within the current views on the future human lunar exploration. We assume the Lunar Gateway in an L2 near rectilinear halo orbit and a landing site at the lunar South Pole; the number of HLS crew of 4; the surface stay time of ~7 days, the payload mass delivered to the surface of 500 kg, and the payload mass returned from the surface of 250 kg. A set of parametric models including an HLS model and an HLS program cost model is developed for the analysis. 39 architectures with varying number of stages (1, 2, and 3 stages) and propellant combinations (LOX/LH2, LOX/CH4, and MMH/NTO) are explored. The Pareto analysis shows that there is a difference between typical performance trends for expendable and reusable architectures. For expendable architectures, the 2-stage option seems to be the most advantageous while, for reusable architectures, the 1- and 3-stage options are either comparable or win over the 2-stage option even for the number of system uses as low as 3. In terms of the propellant combinations, pure LOX/LH2 or combined LOX/LH2/LOX/CH4 architectures dominate the tradespace. Assuming that the inter-stage propellant compatibility is a preferred option for systems refueling from the Gateway, 1-stage and 3-stage all LOX/LH2 architectures are identified as the likeliest candidates to have lowest HLS-related production and launch costs. Further cost analysis of those two architectures shows that the 1-stage HLS wins over the 3-stage system in terms of the overall HLS program cost if a long-term exploration program (on the order of tens of missions) is assumed. Highlights: We present parametric models evaluating human landing systems for lunar exploration. The proposed models account for system reusability and key architectural decisions. We propose an integrated technical and cost analysis of landing system architectures. We discuss engineering tradeoffs in competing human landing system designs. We identify the 1-stage LOX/LH2 system architecture as a preferred design baseline.